2000
DOI: 10.1002/1097-4644(20010201)80:2<223::aid-jcb110>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Environmental acclimatization of the carp modulates the transcription of ?-actin

Abstract: A cascade of mechanisms involving changes in gene expression are substantial to shape the adaptive responses that a eurythermal fish requires upon environmental changes in its habitat. We have previously shown that the cyclical reprogramming of rRNA transcription is a remarkable feature in carp under seasonal acclimatization. Using in situ hybridization and competitive RT-PCR we found significant differences in beta-actin transcripts, generally accepted to be coded by a typical housekeeping gene, in tissues fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…It has been reported that the expression of b-actin gene may be altered by seasonal acclimatization (Sarmiento et al 2000), and serum-stimulation (Schmittgen and Zakrajsek 2000). In this report, Northern blot analysis revealed a significant tissue variation in the expression of b-actin gene in the orange-spotted grouper, indicating that caution should be taken when using b-actin for normalizing gene expression levels among tissues of the orange-spotted grouper.…”
Section: Discussionmentioning
confidence: 62%
“…It has been reported that the expression of b-actin gene may be altered by seasonal acclimatization (Sarmiento et al 2000), and serum-stimulation (Schmittgen and Zakrajsek 2000). In this report, Northern blot analysis revealed a significant tissue variation in the expression of b-actin gene in the orange-spotted grouper, indicating that caution should be taken when using b-actin for normalizing gene expression levels among tissues of the orange-spotted grouper.…”
Section: Discussionmentioning
confidence: 62%
“…As no amplification product was obtained in any of the intestinal segments, the amplification of the β-actin gene was used as an additional internal control to ensure the integrity of the intestinal RNA preparations. The primers, 5′-ggacctgtatgccaacactg-3′ (sense) and 5′-gtcggcgtgaagtggtaaca-3′ (antisense) that allow discrimination of amplification product derived from cDNA and gDNA were used according to the method of Sarmiento et al (2000), essentially using the same conditions described above expect for the annealing temperature (50°C).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Although acclimatization and acclimation show some distinctive features (Segner and Braunbeck, 1990), both require molecular and gene expression adjustments to provide the homeostatic condition that fish need to survive. As a natural physiological process, acclimatization is genetically programmed and involves a recurring seasonal reprogramming of molecular and cellular functions along with a modulation of transcriptional and translational events (On˜ate et al, 1987;Vera et al, 1993Vera et al, , 1997Figueroa et al, 1994;Kausel et al, 1999;Sarmiento et al, 2000). Acclimation also entails differential gene expression (Segner and Braunbeck, 1990;Goldspink, 1995;Tiku et al, 1996;Hirayama and Watabe, 1997;Figueroa et al, 1997;Hirayama et al, 1998;Arends et al, 1998;Ju et al, 2002).…”
Section: Introductionmentioning
confidence: 99%